Public Participation for Constitutional Democracy and Constitutional Governance Based on Law No. 17 of 2014 - Ma’ruf Cahyono (APPTHI, 2018)
The existence of community and regional aspirations is very important in implementing democratic consolidation towards democratic and constitutional governance, so as a technical and substantial supporting element, it is necessary to develop strategies for managing community and regional aspirations to increase public participation optimally. This paper aims to discuss the task of The People Consultative Assembly (Majelis Permusyawaratan Rakyat/MPR) to absorb community aspiration and involve public participation. The analysis was conducted based on Law No. 17 of 2014 concerning the People’s Consultative Assembly (Majelis Permusyawaratan Rakyat/MPR), House of Representatives (Dewan Perwakilan Rakyat/DPR), Regional Representative Council (Dewan Perwakilan Daerah/DPD) and Regional People’s Representative Assembly (Dewan Perwakilan Rakyat Daerah/DPRD) (MD3). This study uses research methods with a qualitative approach. The law stipulates that one of the tasks of the MPR is to review the constitutional system, the Constitution, and its implementation, as well as absorb the aspirations of the people and regions regarding the implementation of the Constitution. The MPR, as a people’s deliberation institution, must be able to respond to the dynamics of aspirations and strengthen people’s sovereignty. This research is also to provide a breakthrough in the optimal management of community aspirations through technology-based change projects. The conclusion of the study found that to be able to achieve these goals; key success factors must be implemented, such as commitment and support from leaders and stakeholders, discipline in time management related to the implementation of the change project agenda that has been made, as well as the adoption and adaptation of best practices of the innovation of existing complementary-collaborative policies. Abstrak Keberadaan aspirasi masyarakat dan daerah sangat penting dalam rangka pelaksanaan konsolidasi demokrasi menuju pemerintahan yang demokratis dan konstitusional, sehingga sebagai unsur pendukung teknis dan substansial perlu disusun strategi pengelolaan aspirasi masyarakat dan daerah untuk meningkatkan partisipasi masyarakat secara optimal. MPR sebagai lembaga permusyawaratan rakyat harus mampu menjawab dinamika aspirasi, sekaligus memperkuat kedaulatan rakyat. Oleh karena itu, penelitian ini mencoba memberikan terobosan dalam pengelolaan aspirasi masyarakat secara optimal melalui proyek-proyek perubahan berbasis teknologi. Penelitian ini menggunakan metode penelitian dengan pendekatan kualitatif, dimana pendekatan kualitatif memiliki tahapan penelitian yang melampaui berbagai tahapan berpikir kritis ilmiah, dimana seorang peneliti mulai berpikir secara induktif yaitu menangkap berbagai fakta atau fenomena sosial melalui observasi di lapangan, kemudian menganalisisnya dan mencoba melakukan penelitian. berteori berdasarkan konteks dari apa yang diamati. Hasil penelitian menyimpulkan bahwa untuk dapat mencapai tujuan tersebut, faktor kunci keberhasilan harus dilaksanakan seperti komitmen dan dukungan dari pimpinan dan pemangku kepentingan, disiplin dalam manajemen waktu terkait pelaksanaan agenda proyek perubahan yang telah dibuat, sebagai serta adopsi dan adaptasi praktik terbaik (best practice) dari inovasi kebijakan kolaboratif komplementer yang ada. Kata kunci: Partisipasi publik, Ketatanegaraan, Kekuasaan legislatif, Demokrasi, UU No 17 Tahun 2014